Sosialisasi Perundungan (Bullying) dan Workshop Pembuatan Media Pembelajaran Berbasis Power Point di SDN 31 Pulau Samatellu Lompo - Rahmat, Muh.; Mahmud, Amrullah; Zaid, Muhammad; Ali, Haedar (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Bullying figures in schools show an alarming trend causing the school environment to be unsafe for students. This can have an impact on the emotional and psychological well-being of children and the overall teaching and learning process. The purpose of this activity is that students are expected to have a better understanding of Bullying, and through a workshop on making learning media based on Power Point, teachers’ abilities in delivering lesson materials can be improved in an interesting way. Method: Data collection was differentiated for students and teachers. Students were assessed through interactive quizzes held after the socialization material, as well as observations of their participation during the session. For teachers, data was collected through observations of involvement during the workshop. This observation aims to assess how active and responsive teachers are in participating in training sessions. The evaluation results of the bullying socialization activity were generally successful. Results: Showing that 89% of students understand the dangers of bullying in the school environment. Meanwhile, the results of the Workshop activity evaluation showed that teachers gained a good understanding in using PowerPoint as a learning aid. Conclusion: Further research is recommended. Further studies can also focus on the effectiveness of ongoing training for teachers in utilizing educational technology and conducting comparisons with other schools to identify factors that influence the success of the program.